Cluster Preface: C–C Activation - Murakami, Masahiro (Synlett, 2018)
Masahiro Murakami received an undergraduate education at the University of Tokyo, and a doctoral degree in science under the supervision of Professor Teruaki Mukaiyama in 1984. He worked for Prof. Mukaiyama as an assistant at the University of Tokyo (1984–1987) and for Prof. Yoshihiko Ito at Kyoto University (1987–1993). He spent ten months (1991–1992) at ETH Zürich as a post-doctoral fellow with Prof. Albert Eschenmoser. After he returned to Kyoto, he was promoted to an associate professor in 1993 and a professor in 2002.